2020
DOI: 10.18597/rcog.3425
|View full text |Cite
|
Sign up to set email alerts
|

Aceptabilidad y seguridad de la copa menstrual: revisión sistemática de la literatura

Abstract: Objetivo: realizar una búsqueda sistemática de la literatura para evaluar la aceptabilidad y seguridad de la copa menstrual como producto de higiene genital femenina. Materiales y métodos: se realizó búsqueda en las bases de datos PubMed, Cochrane Library, Scopus, PopLine y Google Scholar, desde 1966 hasta julio de 2019. Se utilizaron los términos: “Menstrual” AND “Cup” OR “Copa” AND “Menstrual”. Se incluyeron estudios cuantitativos, cualitativos y mixtos, series y reportes de caso publicados en inglés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
12
2
1
Order By: Relevance
“…However, very few clients chose to swap out the reusable pads for the menstrual cup in the study. In contrast to other studies [ 41 , 42 ], we found that, given product choice, menstrual cups were not the preferred MH product among young women in Zimbabwe. The reluctance to opt for and/or use the menstrual cup may be due to an unwillingness to try a novel menstrual product or unwillingness to use an insertable product that may affect their “virginity” [ 28 , 30 , 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, very few clients chose to swap out the reusable pads for the menstrual cup in the study. In contrast to other studies [ 41 , 42 ], we found that, given product choice, menstrual cups were not the preferred MH product among young women in Zimbabwe. The reluctance to opt for and/or use the menstrual cup may be due to an unwillingness to try a novel menstrual product or unwillingness to use an insertable product that may affect their “virginity” [ 28 , 30 , 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that the menstrual cup is an environmentally-friendly option was another reason for participants to use it, as other research has found [ 32 ]. Previous evidence also supports our findings on the acceptability of the menstrual cups as a more comfortable and preferred product, compared to non-reusable products [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite eventual case reports in the literature of complications associated with menstrual collectors, a robust set of recent evidence reinforces our observations, indicating their safety. [3,[27][28][29][30][31][32][33] Additionally, we report a great acceptance of this method by most participants. Claims of initial adaptation difficulties and leaks are consistent with other studies.…”
Section: Discussionmentioning
confidence: 52%